The Complexities of Sexual Consent Among College Students: A Conceptual and Empirical Review. Issue 4 (3rd May 2016) - Muehlenhard, Charlene L.; Humphreys, Terry P.; Jozkowski, Kristen N.; Peterson, Zoë D.
Abstract : Headlines publicize controversies about sexual assault among college students, and universities face pressure to revise their sexual consent policies. What can the social science literature contribute to this discussion? In this article, we briefly discuss reasons for the recent upsurge in attention to these issues, the prevalence of sexual assault among college students, and aspects of college life that increase the risk of sexual assault and complicate sexual consent. We then review the conceptual challenges of defining sexual consent and the empirical research on how young people navigate sexual consent in their daily lives, focusing primarily on studies of U.S. and Canadian students. Integrating these conceptual issues and research findings, we discuss implications for consent policies, and we present five principles that could be useful for thinking about consent. Finally, we discuss some of the limitations of the existing research and suggest directions for future research.